2019
DOI: 10.4102/curationis.v42i1.1974
|View full text |Cite
|
Sign up to set email alerts
|

Preregistration nursing students’ perceived confidence in learning about patient safety in selected Kenyan universities

Abstract: Background Improvement of patient safety in Kenya depends on knowledgeable nurses who are equipped with the clinical safety and sociocultural competences of patient safety. Objectives This study assessed the theoretical and practical learning of these competences as perceived by nursing students. Method A cross-sectional descriptive study was conducted on 178 preregistration Bachelor of Nursing students from two Kenyan universities using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
5
5
0
Order By: Relevance
“…These findings are similar to some studies [37,38,44,46,61,65,66], although other studies reported mixed results, with reported clinical scores being higher than the class scores in more than half of the dimensions [9,45,65]. Classroom ıs perceived as a safe environment of learning about working in multi-professional teams, understanding the system-based nature of patient safety problems [50] and being more confıdent to speak up [66,67]. As 50 % of the student programme is completed in clinical practice, its contribution to professional socialisation is identified.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to some studies [37,38,44,46,61,65,66], although other studies reported mixed results, with reported clinical scores being higher than the class scores in more than half of the dimensions [9,45,65]. Classroom ıs perceived as a safe environment of learning about working in multi-professional teams, understanding the system-based nature of patient safety problems [50] and being more confıdent to speak up [66,67]. As 50 % of the student programme is completed in clinical practice, its contribution to professional socialisation is identified.…”
Section: Discussionsupporting
confidence: 93%
“…In thıs study, overall, students reported that they were more confident in their knowledge about patıent safety gained in the classroom setting than in the clinical setting. These findings are similar to some studies [37,38,44,46,61,65,66], although other studies reported mixed results, with reported clinical scores being higher than the class scores in more than half of the dimensions [9,45,65]. Classroom ıs perceived as a safe environment of learning about working in multi-professional teams, understanding the system-based nature of patient safety problems [50] and being more confıdent to speak up [66,67].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The same conclusion was reached by the study conducted in Kenya in 2019 [ 15 ]: students learned more about patient safety in education than in clinical practice. This shows that there is a problem with the application of theoretical aspects in the practical context.…”
Section: Resultssupporting
confidence: 64%
“…In summary, clinical safety competencies include safety during drug preparation and administration; infection prevention and control; surgical patient safety; and safety in invasive procedures. In addition, socio-cultural patient safety competencies must be implemented, including patient-centered care, teamwork, collaboration, evidence-based practice, improvement of quality, safety and information technology [ 15 ].…”
Section: Resultsmentioning
confidence: 99%